Photocatalytic degradation of rhodamine B, and phenol red dyes using NiMn2O4 nanoparticles prepared by a new approach - Farideh Sedighi; Ali Sobhani-Nasab; Mohsen Behpour; Mehdi Rahimi-Nasrabadi (Journal of Nanostructures, 2019)
NiMn2O4 nanoparticles have been successfully prepared through sol-gel method. The effects of different factors such as the type of solvent, and amino acid temperature were investigated on the size and morphologies of products. The smallest particle size of NiMn2O4 nanoparticles was found to be 25 nm in diameter. The magnetic properties of the samples were also measured by an alternating gradient force magnetometer (AGFM). The optical property of the desired products was investigated by UV–vis diffuse reflectance spectroscopy , and the band gap of product was computed nearly 3 eV. The estimated band gap confirms that this product may be used as a photocatalyst, so the photocatalytic test was conducted by photooxidation of dyes under ultraviolet irradiation and in the presence of NiMn2O4 nanoparricles. The results demonstrated that rhodamine B degradation was about 98 % under ultraviolet light for 80 min. Therefore, the synthesized product can be employed as an effective photocatalyst.